Devir-bird: ecosophy in connections - Catunda, Marta; Reis Rodrigues, Rodrigo [UNESP] (Univ Zulia, 2017)
This article presents an overview of research and activities undertaken in the last decade, in connection with social movements linked to ecology, permaculture, art, dance and how to unfold in artistic works, mapping among other contributions to education environmental. Through a partnership of the Group of Studies Ecological Perspective of Education of the University of Sorocaba/UNISO with the Network of Studies Ecosofia - Eti for the XXI Century see carrying out sensitization practices of the body, artistic, ecological and educational.
Keywords: Education environmental; social movements; sensitization practices